Publicidade sexista à luz do conceito legal de publicidade abusiva previsto no Código de Defesa do Consumidor - Costa, Priscilla Martins de Freitas Almeida (2021)
Having as background the strong influence that advertising has on society and the consequent need to reflect on the values fostered by sexist advertising, this dissertation aims to study the legal frame that sexist advertising has in Brazil. For such purpose, it is necessary to study the concept of sexist advertising, its kinds, social implications, legal framework and parameters that must be observed by the interpreter upon analysis of the legality of an advertisement. As will be explicated in this work, one of the characteristics of sexist advertising is the use of gender stereotypes, however not all advertisements that use such stereotypes can be interpreted as discriminatory or abusive. The purpose of this dissertation, in this sense, is to combine the free expression of thought and free enterprise with other constitutional rights, not so that there is censorship of sexist advertising, but so that through meticulous case-by-case study, a path opens for a scenario in which society and, especially, advertisers, become aware of the need for the advertising message to be more inclusive or, at least, neutral